KERJASAMA SEKOLAH DAN ORANG TUA DALAM MENINGKATKAN PRESTASI BELAJAR SISWA - Wenda, Tiwena; Irianto, Petrus; Sampebua, Mingsep Rante; Masreng, Robert; Gultom, Monika; Mangolo, Ewendi W. (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The implementation of education policies in underdeveloped regions of Papua faces geographical barriers, digital limitations, and highly complex sociocultural dynamics. This study aims to analyze in-depth the collaboration mechanisms between schools and parents at SMP Negeri 1 Tiom, Lanny Jaya, to improve student achievement. Using a qualitative approach with a case study design, data was collected from eleven key informants through purposive sampling and validated using a triangulation strategy and sources. The research steps included participant observation at committee meetings, in-depth interviews regarding parenting patterns, and an analysis of the achievement information system. The research findings revealed that integrating WhatsApp communication with traditional methods such as home visits and contact books was highly effective in breaking down distance barriers and strengthening student discipline. Furthermore, family education through religious forums was proven to increase parents' understanding of the importance of daily learning support. The implementation of an informal talent mapping strategy also stimulated the intrinsic motivation of indigenous Papuan students. Quantitative results showed a tangible impact in the form of an increase in students' average academic scores from 70 to 78 and a significant decrease in absenteeism. The main conclusion confirms that a flexible, transparent partnership model based on the local wisdom of the Lani community is a strategic key in maintaining the sustainability of education services while breaking the chain of poverty in the interior of the Papua Highlands. ABSTRAK Penerapan kebijakan pendidikan di wilayah tertinggal Papua menghadapi hambatan geografis, keterbatasan digital, serta dinamika sosiokultural yang sangat kompleks. Penelitian ini bertujuan menganalisis secara mendalam mekanisme kolaborasi antara pihak sekolah dan orang tua di SMP Negeri 1 Tiom, Lanny Jaya, untuk meningkatkan prestasi belajar siswa. Menggunakan pendekatan kualitatif dengan desain studi kasus, data dihimpun dari sebelas informan kunci melalui teknik purposive sampling dan divalidasi menggunakan strategi triangulasi teknik serta sumber. Langkah penelitian mencakup observasi partisipatif pada rapat komite, wawancara mendalam terkait pola asuh, dan analisis sistem informasi prestasi. Temuan penelitian mengungkapkan bahwa integrasi komunikasi media WhatsApp dengan metode tradisional seperti kunjungan rumah dan buku penghubung sangat efektif meruntuhkan kendala jarak serta memperkuat disiplin siswa. Selain itu, edukasi keluarga melalui forum keagamaan terbukti meningkatkan pemahaman wali murid mengenai pentingnya pendampingan belajar harian. Penerapan strategi pemetaan bakat secara informal juga mampu membangkitkan motivasi intrinsik siswa asli Papua. Hasil kuantitatif menunjukkan dampak nyata berupa kenaikan rata-rata nilai akademik siswa dari skor 70 menjadi 78 serta penurunan angka absensi secara signifikan. Simpulan utama menegaskan bahwa model kemitraan yang fleksibel, transparan, dan berbasis kearifan lokal masyarakat Lani merupakan kunci strategis dalam menjaga keberlanjutan layanan pendidikan sekaligus memutus rantai kemiskinan di pedalaman Papua Pegunungan.